Neurocognitive and functional correlates of mobile phone use in middle-aged and older patients with schizophrenia. (2nd January 2016) - Depp, Colin A.; Harmell, Alexandrea L.; Vahia, Ipsit V.; Mausbach, Brent T.
Abstract : Objectives: Our objective was to examine the association of mobile phone use and ownership with psychopathology, cognitive functioning, and functional outcome in 196 outpatients aged 40 years and older who were diagnosed with schizophrenia. Method: Participants reported their past and current mobile phone use on a standardized self-report scale and they were administered tests of global cognition, functional capacity, and informant-rated functional outcome. Results: The great majority of subjects had used a mobile phone (78%) but few currently owned one (27%). After adjusting for age (mean age 51), any past mobile phone use was associated with less severe negative symptoms, and higher global cognitive performance, functional capacity, and functional outcome. A total of 60% of participants reported being comfortable with mobile phones, but comfort was not associated with any cognitive or functional outcomes. Conclusion: Most of the older patients with schizophrenia have used mobile phones and lifetime mobile phone use is a positive indicator of cognitive and functional status.